PSHYCHOLOGICAL EFFECTS OF INSTAGRAM ON FEMALES: INCREASE IN BODY DISSATISFACTION & FACIAL AUGMENTATION - Hussain, Tanveer; Basit, Abdul; Shahid, Hafiza Farghana (Journal of Peace, Development and Communication, 2021)
Body dissatisfaction and facial augmentation are two alarming concerns in today’s generation. Previously done studies disclosed a sustainable relation between body image issues and media exposure. Statistics shows that 68% of Instagram users are females from the age group of 18-29 years. This research objected to conduct an empirical analysis to find the relationship between Instagram use, body dissatisfaction and facial augmentation. Questionnaire comprising of four parts Instagram Use, Body Image, Body Dissatisfaction and Facial Augmentation was designed for females specifically where the sample size of population was (n=100). Analysis showed that frequent use of Instagram and content like idealized beauty images have a direct effect on females’ mind resulting in body dissatisfaction. Hence the results proved that body dissatisfaction significantly positive relationship with facial augmentation. As body dissatisfaction will rise trend of facial augmentation will grow.